# 1-4. Are the following results correct? Simplify. Assume a, x , and y are not zero. 1. 8x/12 = 1x/3 (8*1,8*3) 2. 15a^3/25a = 3a^3/5a (3a^3*5, 5a*5) 3. 10^3/10^2 = 10 (10^3-2) 4. -x^2y/(-x^2)^2...

1-4. Are the following results correct?

**Simplify. Assume a, x , and y are not zero.**

**1.** 8x/12 = 1x/3 (8*1,8*3)

**2.** 15a^3/25a = 3a^3/5a (3a^3*5, 5a*5)

**3.** 10^3/10^2 = 10 (10^3-2)

**4.** -x^2y/(-x^2)^2 y^2 = I couldn't figure this one out, so I would like some help in the explanation of this problem.

### 1 Answer | Add Yours

#3 correct. Here are the explanations of the problems.

1. 8x/12 can be simplified by 4.

8x `-:` 4 = 2x

12 `-:` 4 = 3

**The correct answer is 2x/3.**

** **

2. 15a^3 / 25a can be simplified by 5.

15a^3 `-:` 5 = 3a^3

25a = 5a

3a^3 / 5a can be simplified using exponential laws. When dividing powers, you subtract the exponents. Note that 5a is actually 5a^1.

a^3 - a^1 = a^2

A positive exponent places the variable in the numerator.

**The correct answer is 3a^2 / 5. **

3. 10^3 / 10^2

10^(3-2)

10^1

10

**The correct answer is 10.**

4. -x^2y/(-x^2)^2y^2

For problems with multiple variables, I recommend dealing with one variable at a time and then combining them at the end.

You must first work the parentheses according to order of operations.

(-x^2)^2

To find the power of a power, you multiply the exponents.

-x^(2*2) = -x^4

So now (just dealing with the variable x), we have...

-x^2 / -x^4

First of all, the negatives cancel, so now we have...

x^2 / x^4 = x^(2-4) = x^(-2)

Because the exponent is negative, x^2 will go in the denominator in the final answer. Now lets work with the variable y.

y / 2y^2

To make things easier, give y a coefficient and exponent of 1.

1y^1 / 2y^2

Set aside the constants (numbers). The final fraction will contain 1 / 2.

y^1 / y^2 = y^(1-2) = y^-1

Because the exponent is negative, y^1 (or simply just y) will go in the denominator of the final answer.

Now we bring the answer together.

We have the fraction 1/2.

We know that x^2 is in the denominator.

We know that y is in the denominator.

**The correct answer is 1 / (2x^2 * y).**

Just as a review, here are the basic exponentials laws:

n^a * n^b = n^(a+b)

n^a `-:` n^b = n^(a-b)

(n^a)^b = n^(a*b)

n^-a = 1 / n^a